ENTREPRENEURIAL MINDSETS IN ROMANIA AND BULGARIA - POPESCU, Nelu Eugen (Annales Universitatis Apulensis Series Oeconomica, 2014)
The aim of this article is to provide a brief overview of the entrepreneurial mindsets in Romania and Bulgaria based on the survey coordinated by European Commission providing some insights into drivers and perceptions on entrepreneurship as well as the role of education in the entrepreneurial activity, highlighting the main changes in the entrepreneurial activity in the last few years in these two countries.